Work Engagement Mediating Job Demands Resources and MSME Performance in Makassar, Indonesia - A. Nur Asri Ainun; Gempita; Ramli Hatma; Rayn Aqmar (Universitas Sulawesi Barat, 2026)
This study examines the influence of job demands and job resources on the performance of Micro, Small, and Medium Enterprises (MSMEs) owners, with work engagement as a mediating variable. Understanding the factors that drive MSME performance is increasingly important, considering the strategic role of MSMEs in supporting regional economic growth and employment. However, empirical evidence regarding the applicability of the Job Demands–Resources framework in the MSME context remains limited, particularly in developing countries. This study employed a quantitative approach using a survey method involving 100 MSME owners in Makassar City. Data were analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that job resources positively contribute to MSME performance, whereas job demands do not significantly influence performance. Job resources were also found to affect work engagement, while job demands showed no significant relationship with work engagement. In addition, work engagement was found to influence MSME performance. Nevertheless, work engagement did not mediate the relationship between job demands and MSME performance, nor between job resources and MSME performance. These findings suggest that the availability of adequate work resources plays a more substantial role in enhancing MSME performance than the level of work demands faced by business owners. This study contributes to the development of the Job Demands–Resources theory within the MSME context and provides practical insights for policymakers and business development agencies in designing interventions aimed at strengthening MSME performance